Faktor Penyebab Stres Pada Relawan Bencana dan Karyawan Dalam Sebuah Organisasi: Sebuah Tinjauan Pustaka - Intan Febrina; Hayatul Khairul Rahmat (Journal of Current Research in Management, Policy, and Social Studies, 2025)
This research aims to study: factors that cause stress in disaster volunteers and employees in an organization, stress management efforts in disaster volunteers, the definition of stress, the definition of work stress, the definition of volunteers, and the definition of disaster. This research uses a literature study method whose content explains the discussion related to the title written by describing it. The findings of this research are that behind the success of a company and the performance of volunteers or employees can cause work stress. The discussion about work stress is not only negative things that are in it, but positive things are also contained in work stress because positive stress is considered important for motivation, adaptation, and reacting to the surrounding environment when someone is unable to cope with unpleasant situations. Most people see stress as something negative. However, stress can help us achieve the best of ourselves.